An atomically efficient, highly stable and redox active Ce0.5Tb0.5Ox (3% mol.)/MgO catalyst for total oxidation of methane. Issue 15 (26th March 2019) - Sánchez, Juan J.; López-Haro, Miguel; Hernández-Garrido, Juan C.; Blanco, Ginesa; Cauqui, Miguel A.; Rodríguez-Izquierdo, José M.; Pérez-Omil, José A.; Calvino, José J.; Yeste, María P.
Abstract : A very low loading mixed CeO2 –TbO x catalyst, supported on MgO, with improved methane total oxidation activity and stability. Abstract : Redox and catalytic performance in total methane oxidation of a nanostructured ceria–terbia catalyst supported on magnesia is presented and compared to that of a pure ceria catalyst supported on MgO. The investigated material, Ce0.5 Tb0.5 O x (3% mol.)/MgO, features several remarkable properties: a quite low total molar loading of the two lanthanide elements, high reducibility as well as very high oxygen storage capacity at low temperatures and higher catalytic activity than MgO-supported CeO2 . In terms of lanthanide atomic content, the catalytic performance of Ce0.5 Tb0.5 O x (3% mol.)/MgO largely improves compared to that of bulk type ceria and ceria–magnesia solid solutions. Such a behavior implies proper optimization of the usage of lanthanide elements. A second contribution to atomic economy in the catalyst design relates to the fact that the novel formulation demonstrates a good stability in the redox and catalytic performance against very high temperature treatments. An investigation of the structure of both the fresh and high temperature-aged catalysts at the atomic scale, by means of complementary aberration corrected microscopy techniques, reveals the occurrence of a variety of highly dispersed, exotic, lanthanide-containing nanostructures, which span from isolated, atomically dispersed, Ln species to nanometer-sized CeTbO2− x patches, extended CeTbO2− x bilayers and 3D CeTbO2− x nanoparticles. Nanoanalytical results evidence the mixing of the two lanthanides at atomic levels in these nanostructures. The combined effects of nanostructuring, mixing of the lanthanides at the atomic level and interaction with the MgO oxide are the roots of the improvement in functional, redox and catalytic properties of the novel Ce0.5 Tb0.5 O x (3% mol.)/MgO catalyst.